Development of Unity 3D Learning Media to Increase Students’ Learning Outcomes and ICT Literacy (Journal of Primary Education, 2019)
This research is based on the students’ learning achievement in science subject of water cycle topic, which was quite difficult for the students. One of the obstacles facing the teacher was learning media that were lacking updates in relevance to current development. The objectives of this research are to develop, to test the validity, to analyze the effectiveness and the practicality of Unity 3D learning media. Research and Development design based on Borg and Gall is used in this research. The product validity test was carried out by experts through data analysis technique in the form of percentages. The product effectiveness test was carried out with a wide-scale trial using a quasi-experimental design through data analysis technique of students’ learning outcomes improvement by using the n-gain test and students’ ICT literacy with percentages, as well as differences in learning outcomes through t-tests. The product practicality test was done by distributing questionnaires for students’ responses by using a data analysis technique in the form of percentages. The results of this research showed that the validation assessment conducted by media experts was 93.1% and by material experts was 87.5%, with very valid criteria. The effectiveness of the product with the n-gain test was 43% (moderate), and the increase in students' ICT literacy was 12%. There was a significant difference in the post-test result of the experimental and control class through the t-test of 4.3%. The practicality of media was 89% (very practical), based on students’ responses. From those results, it can be concluded that the Unity 3D learning media is effective and practical for improving learning outcomes and ICT literacy for fifth-grade elementary school students.